Comprehensive applied sport psychology - Taylor, Jim, 1958- (New York : Routledge, 2019)
The aim of Comprehensive Applied Sport Psychology (CASP) is to challenge our field to look beyond its current status and propel applied sport psychology and mental training forward and outward with a broad and multi-layered examination of everything psychological, emotionally, and socially that the athletic community contends with in pursuit of athletic success and that sport psychologists and mental trainers do in their professional capacities. Comprehensive Applied Sport Psychology is the first professional book aimed at offering a truly expansive and deep exploration of just about everything that applied sport psychologists, consultants and mental trainers do in their work. CASP plumbs the depths of the athletic mind including attitudes, psychological and emotional obstacles, mental "muscles" and mental "tools," quality of sport training, the health and well-being of athletes, and other areas that are essential to athletic success. This new volume examines not only the many ways that consultants impact athletes, but also explores their work with coaches, teams, parents, and interdisciplinary groups such as sports medicine team and sports management. The book is grounded in both the latest theory and research, thus making it a valuable part of graduate training in applied sport psychology, as well as a practical resource for consultants who work directly with athletes, coaches, teams, and parents. The goal of CASP, in collaboration with dozens of the leading minds in the field, is to create the definitive guideto what applied sport psychology and mental training are and do.
OCLC-licensed vendor bibliographic record.
Keywords: SPORTS & RECREATION / Sports Psychology; PSYCHOLOGY / Applied Psychology; SPORTS & RECREATION / Coaching / General; Sports -- Psychological aspects; Coaching (Athletics); Psychology, Applied